Lactobacillus Sepsis and Probiotic Therapy in Newborns: Two New Cases and Literature Review - Dani, Carlo; Coviello C, Caterina; Corsini I, Iuri; Arena, Fabio; Antonelli, Alberto; Rossolini, Gian Maria (American Journal of Perinatology Reports, 2016)
Many term and preterm infants are commonly supplemented with probiotics to prevent adverse effects of antibiotic administration and necrotizing enterocolitis and they are believed to be safe. However, the supplementation with Lactobacillus rhamnosus GG has been associated with the development of sepsis with a cause–effect relationship in six newborns and children. In this study, we report two further cases and discuss the emerging issue of probiotic supplementation safety in neonates. We conclude that physicians must be aware that supplementation with L. rhamnosus GG can cause sepsis in high-risk patients on rare occasions.
Keywords: lactobacillus; probiotics; infection; sepsis; infant